In Search of the Sorcerer’s Apprentice: between Lucian and Walt Disney - KALITAN, DAMIAN (Journal of Education Culture and Society, 2020)
At fi rst glance, the movie by Jon Turteltaub entitled The Sorcerer’s Apprentice (2010) seems not to have any connections with Greco-Roman antiquity whatsoever. To fi nd the hidden connection we have to go back to year 1797 when Johann Wolfgang Goethe publi-shed his famous ballad Der Zauberlehrling (The Sorcerer’s Apprentice)Almost a century later, this work inspired a French composer Paul Dukas to write his masterpiece, the sympho-nic scherzo L’apprenti sorcier. Dukas’ music became the leitmotif of both Disney’s movies: Fantasia (1940) and Fantasia2000 (1999) whose action is based on Goethe’s ballad. Also, the basic elements of the plot were used in one of the episodes of the series Alfred Hitchcock Presents (1961). This is where we touch the ancient roots of the story. A good friend of J.W. Goethe, Christoph Martin Wieland, happened to have published in 1789 the fi rst complete German translation of Lucian of Samosata’s (120-180 AD) works, including a dialogue entitled Philopseudes (The Lover of Lies). The tenth story told in Philopseudes turned out to be very similar to the one written by J. W. Goethe and then adapted into Disney’s and Turteltaub’s movies. In my paper I try to show the transmission of the Lucianic text from antiquity to modern fi lm adaptations. The original Lucian tale, rewritten by J.W. Goethe, becomes very infl uential. The so-called “sorcerer’s apprentice syndrome” can be found at the root of many fantastic stories in which humans could not curb their creations (i.e. robots) which eventually would turn against their makers. The primary focus of this paper is on how the story of a young apprentice changed over centuries and how it was adopted by cinematography.